A LOOK AT THE HURDLES FACED BY FEMALE ATHLETES IN SPORTS-BASED FILMS IN BOLLYWOOD - Tiwari, Shweta; Shrivastava, Garima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The depiction of female athletes in Hindi sports films has notably progressed, transitioning from peripheral positions to prominent pivotal figures. Films like Chak De! India, Dangal, Mary Kom, Panga, and Saala Khadoos explore the many problems encountered by women in sports, encompassing gender discrimination, societal expectations, and personal sacrifices. These films confront and contest dominant gender stereotypes while advocating a narrative of empowerment, resilience, and the dismantling of barriers. These films, by highlighting the challenges and successes of female athletes, have facilitated societal transformation and enhanced the acceptability of women in athletics.